2013
DOI: 10.1124/jpet.113.209643
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of hERG Channel Block by the Psychoactive Indole Alkaloid Ibogaine

Abstract: Ibogaine is a psychoactive indole alkaloid. Its use as an antiaddictive agent has been accompanied by QT prolongation and cardiac arrhythmias, which are most likely caused by human ether a go-go-related gene (hERG) potassium channel inhibition. Therefore, we studied in detail the interaction of ibogaine with hERG channels heterologously expressed in mammalian kidney tsA-201 cells. Currents through hERG channels were blocked regardless of whether ibogaine was applied via the extracellular or intracellular solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 56 publications
2
32
0
1
Order By: Relevance
“…The mean effect on QTcI was 28 milliseconds in the 120-mg dose group and 42 milliseconds in the 180-mg group, changes that would be clinically concerning in a clinical setting and would require ECG monitoring in subsequent clinical trials. 13 Ibogaine is rapidly converted to noribogaine in humans with peak noribogaine levels of 18.7 ng/mL after an oral dose of 20 mg in CYP2D6 extensive metabolizers, 14 and we would predict that an ibogaine dose of 286 mg would lead to noribogaine C max values comparable to those observed in patients receiving 180 mg noribogaine. Exposure response (ER) analysis was consistent with the observed QT prolongation in the by-time-point analysis across dose groups; ER analysis can therefore be used to predict the QT effect in future clinical trials to optimize the benefit/risk of noribogaine treatment in opioid-dependent subjects seeking treatment.…”
Section: Discussionmentioning
confidence: 94%
“…The mean effect on QTcI was 28 milliseconds in the 120-mg dose group and 42 milliseconds in the 180-mg group, changes that would be clinically concerning in a clinical setting and would require ECG monitoring in subsequent clinical trials. 13 Ibogaine is rapidly converted to noribogaine in humans with peak noribogaine levels of 18.7 ng/mL after an oral dose of 20 mg in CYP2D6 extensive metabolizers, 14 and we would predict that an ibogaine dose of 286 mg would lead to noribogaine C max values comparable to those observed in patients receiving 180 mg noribogaine. Exposure response (ER) analysis was consistent with the observed QT prolongation in the by-time-point analysis across dose groups; ER analysis can therefore be used to predict the QT effect in future clinical trials to optimize the benefit/risk of noribogaine treatment in opioid-dependent subjects seeking treatment.…”
Section: Discussionmentioning
confidence: 94%
“…It is known that hERG blockers binding to the central cavity require the channel to be opened in order for the drug to access the central cavity. Some previous studies have reported that high‐affinity hERG blockers exhibit preferential binding to the open‐inactivated state of the channel, rather than its open state. This agrees with the findings from other studies that the inactivation‐deficient mutations showed a reduction in the hERG block by drugs, such as E‐4031, dofetilide, and RP58866.…”
Section: Herg Channel: Structural Topologymentioning
confidence: 98%
“…The Loewe and Bliss DDI model assume the same or different binding sites within channel pore for simultaneously acting channel blockers. Since erythromycin [5, 7] and possibly clarithromycin [6] bind to the external domain of hERG channel protein, while terfenadine [21], fluoxetine [14, 28], fluconazole [13], ketoconazole [29, 30, 32], paroxetine [22] and presumably itraconazole bind to internal domain of hERG channel pore, the Bliss and Loewe model, respectively, should perform better for those groups of drugs. This is not the case according to the results obtained it this study.…”
Section: Discussionmentioning
confidence: 99%